MRMR museum registration methods - Simmons, John E. editor; Kiser, Toni M. editor (Rowman & Littlefield, 2020)
Since the first edition was published in 1958, Museum Registration Methods has defined the profession and served as a fundamental reference to all aspects of collections registration, care, and management. The sixth edition of Museum Registration Methods is a comprehensive guide to registration and collections management for museums, from acquisition to use and deaccessioning. The authors and other contributors come from a wide variety of museums and specializations. The 56 chapters in this edition are either new or updated, and include the history of the profession, the role of the registrar in the museum, managing very large collections, developing and implementing collection management policies, documentation of collections, accessioning, condition reports, deaccessioning, repositories, and provenance research. Contemporary and digital art, living and natural history collections, loans, exhibitions, found-in-collection objects, shipping, records management, and electronic data management are also addressed, along with object handling and numbering, digitization, condition reporting, preventive care, storage on and off-site, inventory, moving and packing, shipping nationally and internationally, couriering, risk assessment, security, insurance, integrated pest management, ethics, sustainability, sacred and culturally sensitive objects, intellectual property rights, appraisal, ethical and legal issues, and research. The book includes a comprehensive resource list, glossary, hypothetical situations to ponder, and model collection forms.